Pertumbuhan Distribusi, Ukuran Kelompok, dan aktivitas Kerak Kerbau (Acridotheres javanicus Cabanis, 1851) dan Kerak Perut-Pucat (Acridotheres cinereus Bonaparte, 1850) di Kota Manado dan Kabupaten Minahasa Utara, Sulawesi Utara - Saroyo; Parluhutan Siahaan; Seni Tongkukut; Adelfia Papu (Universitas Sam Ratulangi, 2024)
Research on growth distribution, group size, and activity of javan myna [Acridotheres javanicus (Cabanis, Jl 1851)] and pale-bellied myna [Acridotheres cinereus Bonaparte, CLJL 1850] in Manado City and North Minahasa Regency, North Sulawesi, was carried out from July 2021 to June 2023. The aim of the study was to examine the geographical distribution of javan myna and pale-bellied myna in Manado City and North Minahasa Regency after the last survey conducted by Tasirin & Fitzsimons [23], determine group size, and analyze their activities. The research method used is a survey by determining the location, the number of individuals, or the number of birds in a group (group) when found and doing activities together, as well as bird activity during encounters, which are classified according to the classification applied to the Bali starling (Leucopsar rothschildi) [22]. The results showed that javan myna was scattered in only a few locations in Manado City and North Minahasa Regency, while pale-bellied myna was widely distributed with a tendency to approach residential areas and urban areas. The herd sizes observed during the survey were 3 individuals for javan myna and 1-25 individuals for pale-bellied myna. Activities observed during the survey included flying, walking, foraging, eating, drinking, socializing and caring for children, vocalizations, perching, and nesting. With these results, it can be concluded that the javan myna has low adaptability and growth compared to the pale-bellied myna, which has a very high adaptation to human life, so that it can survive and thrive in Manado City and North Minahasa Regency and take advantage of the resources built humans, such as using the tops of churches, houses, and buildings for nesting sites, doing activities close to human activities, and using household waste as food. With these results, it is important to analyze the effect of population growth and distribution of javan myna, especially for the benefit of conserving local species in other Sturnidae.